PAIRED DIFFERENCE ANALYSIS OF STARTUP BUSINESS NEGOTIATION: STATED & IN-PRACTICE STRATEGY - Syujana, Alvin; Hermawan, Pri (Journal of Business and Management, 2018)
Abstract. The need to understanding and possessing negotiation is very important since it is every day process involving future of the orgsanization. Meanwhile, it is become more important to startup, as an enterprise unit who have characteristic of small team of professionals that hold autnomy authority. In this study, it asked what strategy between those they stated, which consist soft & hard, and integrative. However, a good negotiator should able to implement the strategy to deliver a desirable outcome. Therefore, an issue to measure consistency of stated and in-practice strategy is raised. Two questions is developed: is there a difference between stated & in-practice negotiation strategy and if difference is exist what is the direction. A model of measurement is developed consist of 24 pairs consist of each strategy in negotiation dimension. The research indicate 11 out of 24 pairs have evidence of difference and 7 out of 8 integrative pairs indicate the strategy less likely than what expected. Meanwhile, 4 rest soft & hard pairs with difference shows positive direction. The result of this research indicate an overconfident and innability to perform integrative strategy existing in the sample and many respondent of the sample doesn’t recognize what integrative negotiation is. Keywords:  Distributive, Integrative, Negotiation Strategy, Paired Difference Test, Startup Business,